RANCANG BANGUN E-PERPUSTAKAAN DI SMA NEGERI 16 BATAM DENGAN CODEIGNITER - Gulo, Erni Heppy; Saragih, Saut Pintubipar (Computer Science and Industrial Engineering, 2023)
Technology development growth globally has continue to strive to work more effectively and efficiently. One solution is to computerize systems that were previously conventional. In this case, the use of the website can help the library to be more effective. In this study a web-based library application was built using the CodeIgniter Framework. With this system, it is hoped that it can meet various user needs, such as searching for books, recording member data, recording book data, returning books, calculating fines, borrowing books and preparing reports. The system development methodology used in this study is the software development method with the Extreme Programming model. The system was built using the Hypertext Pre Processor (PHP) programming language and MySQL database. The results of this research are that the web-based library information system is intended for library students and staff with a user-friendly web interface, users can search for books, borrow, return, managing library members becomes more practical. In designing a library information system, there are additional features that are quite important, such as data reports on books, members, transactions and fines that can assist in monitoring and making decisions related to library management.